PREMAN POLITIK DAN PASAR: ANCAMAN KEAMANAN TERHADAP IKLIM INVESTASI INDONESIA - Nurdin, Ali; Suciyati Sartika, Nenden; Dasmaran, Verliani; Nurbani, Siti (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2025)
The phenomenon of thuggery in Indonesia is a complex problem that is rooted in the socio-political and economic structure of this country. This article aims to analyze the relationship between thuggery and political parties, as well as examine its impact on Indonesia's investment climate and global competitiveness. The research was conducted with a qualitative-descriptive approach, using secondary data obtained from literature studies, international agency reports, the latest government policy analysis, and equipped with a systematic luterature review (SLR) on related themes. The findings of the study show that thuggery evolved from a long history from the colonial era to the reform period, with a pattern of close relationships between thugs and political elites through networks of patronage and political clientelism. Thuggery is also used intensively as a tool of mass mobilization and an instrument of intimidation in electoral competitions. The impact on the investment climate is significant, as it creates additional costs in the form of illegal levies and intimidation, lowers investor confidence, and weakens Indonesia's competitiveness compared to neighboring countries such as Vietnam, Malaysia, and Thailand. The government has implemented a number of important policies, including the establishment of the Thugs Task Force by President Prabowo Subianto in May 2025, to overcome thuggery and create better stability for the business world. However, major challenges are still faced such as the involvement of officials, strong networks of thugs, and weak community participation. This article recommends strengthening synergy between the government, law enforcement, the business world, and the wider community through regulatory reform, increased transparency, and strict supervision. This step is expected to effectively reduce the negative impact of thuggery, improve the investment climate, and lift Indonesia's global competitiveness in the long term.